Molecular Magnet Based on a Thiocyanato-Bridged Heterobimetallic Complex: Synthesis and Magnetic Properties - Bi, Jian-Hong; Bi, Wen-Tao; Hu, Nai-Liang (Asian Journal of Chemistry, 2011)
One new self-assembled heterobimetallic complex with the composition CuL-Co(SCN)4 (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradeca-4,11-diene) has been prepared and characterized by IR spectra and elemental analysis. The molecular magnetic properties of the complex were characterized by magnetic susceptibility and presents a antiferromagnetic interaction between the tetraaza macrocycle Cu(II) ions and Co(SCN)42- through the thiocyanatobridged in the complex.